EXPERIMENTAL RESEARCH ON OPTIMAL PLACEMENT OPTIONS OF HEAT EXCHANGE SURFACES IN THE HEAT ACCUMULATOR PARAFFIN-BASED - Antypov, Е. (Energy and Automation, 2016)
The design of the heat accumulator phase transition and an experimental study of its effectiveness. We analyze the importance of the dynamics of temperature fields and heat flux distribution in the heat accumulator, and received placement of the boundary distance of heat transfer surface in the case of the object.